Management of Thrombotic Antiphospholipid Syndrome - Chighizola, Cecilia Beatrice; Raimondo, Maria Gabriella; Meroni, Pier Luigi (Seminars in Thrombosis and Hemostasis, 2018)
Persistent serum positivity for antiphospholipid antibodies (aPL) is required to diagnose antiphospholipid syndrome (APS), an autoimmune disease characterized by recurrent vascular thrombosis and/or pregnancy morbidity. The current therapeutic management of patients with thrombotic APS aims at preventing recurrences and long-term complications by attenuating the procoagulant state. There is overall consensus to reserve moderate-intensity anticoagulation to aPL-positive patients with a previous venous thrombosis; the therapeutic options for those with a history of arterial event comprise antiplatelet agents and high-intensity anticoagulation. Unfortunately, thrombotic occurrences might occur despite adequate anticoagulation, carrying a significant burden of morbidity and mortality. The management of refractory thrombotic APS and catastrophic APS is still not clear, warranting the issue of recommendations. Vitamin-K antagonists are limited by significant side effects, and a careful weighting of risks and benefits should be performed to reserve the optimal treatment to each patient. To overcome these limitations, novel oral anticoagulants have been introduced in the market, but their efficacy in thrombotic APS has still to be unraveled. The poor safety profile and the scarce efficacy of drugs acting on the coagulation cascade explain why novel therapeutic approaches are currently under investigation, to identify pharmacological tools specifically counteracting aPL-mediated prothrombotic effects.
Keywords: antiphospholipid antibodies; antiphospholipid syndrome; thrombosis; treatment